A dilemma for the welfare state: managing the cost for shorter working hours, 1919–2002. (1st January 2017) - Spross, Linn
Abstract: The purpose of this article is to study how the Swedish welfare state has managed the cost of shorter working hours. During the twentieth century, several official reports were published in order to produce knowledge about this issue and to deal with the cost for the reform. This article aims to examine the arguments and beliefs of the political economy of the welfare state that emerge from these formulations. An examination of shorter working hours as social policy sheds new light on the relationship between the welfare state and capital, in addition to limits for social policy imposed by the economic system. A reduction of work hours has never been justified as a reform that simply gives more time for leisure and less time for work, but has been assigned a cost that was necessary to manage. The reform was considered possible because it was interpreted as helping to reproduce labor power or capitalism as a whole. It was thought impossible and undesirable when considered to be a threat to this reproduction. This article shows the process of managing the cost for shorter working hours in Sweden and how arguments fundamentally changed over time, although the basic premises remained the same.